Sibling relationship dimensions: A phenomenological study on identical twin children - Afifatunnisa, Annida; Kristiana, Ika Febrian; Masduki, Yusron (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2024)
Sibling relationships have a significant impact on individual development within twin dynamics. A strained sibling relationship between twins can evoke feelings of comparison, discomfort, jealousy, and even hostility, thus either deepening or widening the chasm between them. This study aims to delineate the dimensions of sibling relationships among twins. Employing a qualitative approach with a phenomenological study design, the research enlisted four participants, comprising two sets of identical twins aged 21-25 years. Data collection methods included observation and semi-structured interviews. Descriptive Phenomenological Analysis (DPA) was utilized for data analysis. The study revealed two major themes encapsulating the dimensions of sibling relationships: affection and conflict.